Gen Z’s Perception of Social Media Profile Pictures from a Baudrillardian Perspective and Fashion Magazine Cover Images of Digital Habitus - Lee, Yoon Kyung (International Journal of Costume and Fashion, 2024)
The significance of portraiture as a mode of visual communication and expression has remained unabated through the ages. The extent to which portraiture meets this expectation is often debated. Who is responsible for interpreting an image has become an important question. This study analyzes personal profile photos on social media and fashion models’ magazine cover images based on the framework of the analysis of hyper-realism in fashion from the perspective of digital habitus.. This study offers alternatives and solutions to social change by examining various social problems such as lack of identity, digital vulnerability, and digital habitus that are prevalent in the present digital society from the perspective of hyperreality-based fashion acceptance. KCI Citation Count: 0